2020
DOI: 10.1016/j.ophtha.2019.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Treatment of Amblyopia

Abstract: Purpose: To review the published literature assessing the efficacy of binocular therapy for the treatment of amblyopia compared with standard treatments.Methods: Literature searches with no date restrictions and limited to the English language were conducted in January 2018 and updated in April 2019 in the PubMed database and the Cochrane Library database with no restrictions. The search yielded 286 citations, and the full text of 50 articles was reviewed. Twenty articles met the inclusion criteria for this as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
(58 reference statements)
0
35
0
Order By: Relevance
“…Age turned out to be a key factor in determining eligibility and success of dichoptic treatment in practice. In the literature, the age of children undergoing these therapies mostly range from 4 to 17 years [10]. We note that the subjects from the study of Gambacorta et al, which used the same gaming principles, had older subjects with an age range of 7 to 17 years [17].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Age turned out to be a key factor in determining eligibility and success of dichoptic treatment in practice. In the literature, the age of children undergoing these therapies mostly range from 4 to 17 years [10]. We note that the subjects from the study of Gambacorta et al, which used the same gaming principles, had older subjects with an age range of 7 to 17 years [17].…”
Section: Discussionmentioning
confidence: 85%
“…A number of studies have reported favourable results not only in children but also in adults with on average 1 to 2 logMAR lines of improvement [9,10]. However, studies comparing the effectiveness of behavioural training with patching were incomplete because the actual gaming time was compared to prescribed or reported patching time [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…36 Several literature reviews have specifically compared the efficacy of binocular treatments to patching. A review by Pineles et al did not recommend the use of binocular treatments, 33 while other systematic literature reviews concluded that more research was required before making any conclusions about binocular treatments. 34 51 More RCTs were available at the time of our literature search than these studies, but the overall strength of evidence for this comparison was low, which implies that further research is still required.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of vision-based treatments for patients with amblyopia have been examined in systematic reviews comparing patching against atropine [29][30][31] or binocular treatments against patching. [32][33][34] Only one review 35 included a meta-analysis, which was limited to two studies and two treatments. In general, published systematic reviews and meta-analyses found no significant differences between the various vision-based amblyopia treatments.…”
Section: Key Messagesmentioning
confidence: 99%
“…It improves not only binocular vision Hess and Thompson, 2015;Webber et al, 2016;Kelly et al, 2018) but also monocular acuity (Hess et al, 2010bTo et al, 2011;Li et al, 2013Li et al, , 2014Mansouri et al, 2014;Birch et al, 2015). Despite ongoing debate concerning which therapeutic approach is more effective (Holmes et al, 2016;Kelly et al, 2016;Gao et al, 2018;Manh et al, 2018;Pineles et al, 2019), one should bear in mind the possibility that the visual improvements from both approaches might involve the same mechanisms in the brain. If both approaches involve similar neural mechanisms, convenience and efficacy might determine which one to use.…”
Section: Introductionmentioning
confidence: 99%